Record of Pinus discolor Bailey et Hawksworth in the Sierra de Monte Grande, San Luis Potosí, Mexico - Avila Naranjo, Jose Antonio; Garcia Moya, Edmundo; Reyes Agüero, Juan Antonio (Instituto de Ecología, A.C., 1992)
The presence of a Pinus discolor forest in an isolated sierra of north central San Luis Potosí state has been confirmed. Position of stomata on both leaf surfaces, leaf length, number of leaves per fascicle, height, basal diameter of the shrubs and cone size correspond to the characteristics of this species. On the other hand, plant height and number of leaves per fascicle increased slightly the known species variation in other pinyon forests.